Local nearrings on finite non-abelian $2$-generated $p$-groups - Raievska, I.Yu.; Raievska, M.Yu. (Carpathian Mathematical Publications, 2020)
It is proved that for ${p>2}$ every finite non-metacyclic $2$-generated p-group of nilpotency class $2$ with cyclic commutator subgroup is the additive group of a local nearring and in particular of a nearring with identity. It is also shown that the subgroup of all non-invertible elements of this nearring is of index $p$ in its additive group.